Contribution of outstanding teachers from Western Ukraine of late XIX - early XX century to development of theory and methods of teaching history - Zinoviia Nahachevska; Yurii Hryvnak (Vasyl Stefanyk Precarpathian National University, 2017)
The article provides analysis of theses from works of prominent representatives of educational thought in Western Ukraine of late XIX - early XX century, which are related to solving problems of teaching history in elementary and secondary schools in the region. The emphasis is placed on the actualization of content and methods of teaching by V. VilshanetskaZhukovetska, A. Kopystianskyi, M. Korduba, and K. Malytska. Key words: elementary and secondary schools (gymnasia), curricula, content, principles and methods of teaching history, school textbooks, anthropologization and humanization of history, study of local lore.